Functions of collective victimhood: Political violence and the case of the Troubles in Northern Ireland. Issue 2 (May 2018) - Lynch, Orla; Joyce, Carmel
The conflict that played out in Northern Ireland between 1969 and 1998 is commonly referred to as the Troubles. Over the course of almost 30 years just under 3, 700 people were killed and an estimated 40, 000–80, 000 injured; it is thought that 80% of the population of Northern Ireland knew someone who had been killed or injured in the violence. The protracted conflict that played out between local communities, the state and paramilitary organisations left a legacy of community division in the region; competing narratives of victimhood emerged and they served to inform intergroup relations. This article will provide a brief overview of the functions of collective victimhood as manifested in the social psychological literature, drawing on the example of the Troubles in Northern Ireland as a case study. In doing so, we will focus particularly on the mobilisation of collective victimhood as both a precursor for involvement in conflict but also as a justification after the event. Additionally, we are interested in the superordinate (broad societal level) re-categorisations of subgroups based on collective identities, including victimhood, and how they can be used as a conflict transformation resource. Ultimately, we will argue that research has tended to overlook how those involved in (as well as those impacted by) the Troubles construct and mobilise victimhood identities, for what purpose and to what end. We argue that in order to understand how collective victimhood is used and to understand the function it serves, both as a precursor for involvement in conflict and as a conflict transformation resource, we need to understand how parties to the conflict, both victims and perpetrators, construct the boundaries of these identity categories, as well as their rhetorical counterpart perpetrators of political violence.